UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MEDIA DAN METODE PEMBERIAN TUGAS DI KELAS IVB SDN 007 BAGAN BESAR DUMAI - Syafrudin, Syafrudin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2015)
This study aimed to describe the learning outcomes through the use of maps. The subjects were students of class V SD 007 Bagan Besar, Dumai with held consisting of two cycles. Improved learning outcomes in terms of four categories, namely absorption, the effectiveness of learning, mastery learning completeness students both individually and classical completeness and thoroughness of learning outcomes. The instrument used for data collection is an oral test and a written test in the form of worksheets that is done after the process of learning. The results showed absorption learning outcomes on average 80% considered very good, very effective learning effectiveness categorized by an average of 8.5. While the completeness of student learning outcomes expressed complete 100%.Keywords: maps, learning outcomes